Comparison Between Classic and Fuzzy Logic Method on Corrosion Rate of Zinc Metal in Diluted Sulphuric Acid After Nitridation Process - S. Simbolon (Atom Indonesia, 2006)
Nitridation of zinc metal in DC nitridation machine by varying temperature from 150oC to 300oC and time of nitridation from 15 to 75 minutes were carried out. Nitrided zinc metal were corroded in diluted sulfuric acid solution in room temperature. The relationship between corrosion rate of zinc metal with temperature and time of nitridation were described in classic method.  The results found were not satisfied because it contained ambiguous, uncertainty and imprecision data. The relationship of two inputs and one output were also described by using Fuzzy Logic. The performance of Fuzzy Logic has been carried out through triangular, S and Z shape membership function for two inputs temperature and time respectively, and one output corrosion rate or ICorr. Meanwhile two trapezoidals and one triangular were used for output corrosion rate. Nine rules were used to perform defuzzyfication, and it was also described three dimensions relationship between temperature, time of nitridation and corrosion rate.  The results found  that maximum corrosion rates were found in the three parts, but the lowest corrosion rate was found at the middle temperature and the lowest time of nitridation as shown in the surface viewer